Keen in technical field, Zek Aman can build drones - Nor Salwana, Mohammad Idris (2021)
PEKAN, 12 May 2021 - Often we see many people fly drones not only as a hobby but for various purposes such as search and rescue, surveillance, monitoring traffic and weather conditions, fire-fighting and farming.